2013
DOI: 10.1103/physrevb.87.121406
|View full text |Cite
|
Sign up to set email alerts
|

Third harmonic generation in graphene and few-layer graphite films

Abstract: We observe optical third harmonic generation from graphene and few-layer graphite flakes produced by exfoliation. The emission scales with the cube of the intensity of the incident near-infrared femtosecond pulses and has a wavelength that is one-third of the incident wavelength, both consistent with third harmonic generation. We extract an effective third-order susceptibility for graphene that is on the order of 10 −16 m 2 /V 2 , which is comparable to that for materials that are resonantly excited, but large… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
252
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(267 citation statements)
references
References 65 publications
13
252
1
1
Order By: Relevance
“…For comparison, we note that the third-order susceptibility of extended graphene without the involvement of any plasmons has been measured via four-wave mixing experiments as |w (3) |B10 À 7 esu, exceeding the maximum value obtained for a 4-nm-thick gold film measured under the same experimental conditions 20 . In addition, THG measurements have yielded values |w (3) |B10 À 8 esu in graphene 22 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison, we note that the third-order susceptibility of extended graphene without the involvement of any plasmons has been measured via four-wave mixing experiments as |w (3) |B10 À 7 esu, exceeding the maximum value obtained for a 4-nm-thick gold film measured under the same experimental conditions 20 . In addition, THG measurements have yielded values |w (3) |B10 À 8 esu in graphene 22 .…”
Section: Resultsmentioning
confidence: 99%
“…For comparison, we note that the third-order susceptibility of extended graphene without the involvement of any plasmons has been measured via four-wave mixing experiments as |w (3) |B10 À 7 esu, exceeding the maximum value obtained for a 4-nm-thick gold film measured under the same experimental conditions 20 . In addition, THG measurements have yielded values |w (3) |B10 À 8 esu in graphene 22 .The linear and nonlinear spectral lineshapes display a dependence on light intensity that is clearly observable above B1 GW m À 2 , as shown through time-domain simulations in Fig. 2d-f, obtained from the Fourier transform of the induced dipole over an optical cycle after reaching a steady-state regime (see Methods).…”
mentioning
confidence: 93%
“…A recent study experimentally demonstrated THG from graphene for transitions occurring near the K point and was carried out at normal-incidence angle; in that study, the authors report a quadratic dependence of THG on graphene layer number [40]. In contrast, the present work reports experimental THG from graphene under conditions in which the TH is in three-photon resonance with the M point of graphene and at non-normal-incidence angle in order to provide access to other nonlinear susceptibility elements not accessible under a normal-incidence configuration, and to probe thicker films, in the case of multilayer graphene.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its gapless, linear charge-carrier dispersion relation [3,4], graphene is capable of relatively strong, broadband coupling with light [5,6], and offers a large electrically-tunable optical response [7]. Valence and conduction electrons in this material present a uniform velocity that clearly emphasizes their anharmonic response to external fields, which has stimulated considerable interest in the graphene nonlinear optical properties [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Further motivation to study optical nonlinearities in monolayer graphene is provided by the availability of interband optical transitions within a continuous range of low photon energies, accompanied by a high electrical mobility [24,25].…”
Section: Introductionmentioning
confidence: 99%